Structural and optical properties of Tin Oxide and Indium doped SnO2 thin films deposited by thermal evaporation technique - Noaman, Sura Ali; Kadhim, Rashid Owaid; Hussain, Saleem Azara (JOURNAL OF ADVANCES IN PHYSICS, 2016)
Tin Oxide and Indium doped Tin Oxide (SnO2:In) thin films were deposited on glass and Silicon substrates by thermal evaporation technique. X-ray diffraction pattern of pure SnO2 and SnO2:In thin films annealed at 650oC and the results showed that the structure have tetragonal phase with preferred orientation in (110) plane. AFM studies showed an inhibition of grain growth with increase in indium concentration. SEM studies of pureSnO2 and Indium doped tin oxide (SnO2:In) ) thin films showed that the films with regular distribution of particles and they have spherical shape. Optical properties such as Transmission , optical band-gap have been measured and calculated.